Pembelajaran Ekstrakurikuler Paduan Suara: Analisis Implementasinya di Madrasah Aliyah Negeri (MAN) 2 Jember - Istifadah Istifadah (STAIFAS-Press, 2018)
ABSTRACT The purpose of this research is to figure out and describe choir learning on extracurricular activity in State Senior High School of Jember and to know supporting factors and inhibiting factors of choir extracurricular learning process in State Senior High School of Jember. The result of this research showed that choirn extracurricular learning in State Senior High School of Jember: (1) has the purpose to improve musical intelligence and sharpen the cognitive, affective and psychomotor aspects of thestudents(2) the material of chir extracurricular learning in State Senior High School of Jember is devided into each voice group , such as sopran, altor, tenor and bass, (3) the used method in choir learning is vary, such as plus lecture method, demonstration method, and drill method, and (4) music learning evaluation in State Senior High School of Jember is open and able to motivate students to be more vigorous in exercise. The supporting factors of band learning in State Senior High School of Jember are interest and talent, motivation, infrastructure, school community and parents and the program. While inhibiting factors are emotion and limitedtime. Keywords:Â Learning, Extracurricular, Choir